Exploring the biotechnologial applications in the archaeal domain - Alquéres,S.M.C. (2007)
Archaea represent a considerable fraction of the prokaryotic world in marine and terrestrial ecosystems, indicating that organisms from this domain might have a large impact on global energy cycles. The extremophilic nature of many archaea has stimulated intense efforts to understand the physiological adaptations for living in extreme environments. Their unusual properties make them a potentially valuable resource in the development of novel biotechnological processes and industrial applications as new pharmaceuticals, cosmetics, nutritional supplements, molecular probes, enzymes, and fine chemicals. In the present mini-review, we show and discuss some exclusive characteristics of Archaea domain and the current knowledge about the biotechnological uses of the archaeal enzymes. The topics are: archaeal characteristics, phylogenetic division, biotechnological applications, isolation and cultivation of new microbes, achievements in genomics, and metagenomic.